Digital Transformation and Sustainability: Unraveling Interconnections and Challenges through Bibliometric Insights - Sandy Afriyano Althaf; Sulis Sustyaningsih; Arya Mada Nata Kusuma; Alya Ghaitsa Anwar; Ellen Oktanti Irianto; Muhammad Ramadhani Kesuma (Universitas 45 Surabaya, 2025)
This study investigates the dynamic interconnection between digital transformation and sustainability by employing a bibliometric analysis based on publications indexed in the Scopus database. Using VOSviewer, this research maps keyword co-occurrence networks, identifies thematic clusters, and examines research evolution from 2000 to 2024. The results reveal that “digital transformation” and “sustainable development” form the central core of the research landscape, strongly linked with emerging technologies such as artificial intelligence, Internet of Things (IoT), blockchain, big data, and smart manufacturing. These technologies are shown to facilitate environmental efficiency, green innovation, and the advancement of sustainable business models. Over time, research trends have shifted from early industrial digitalization themes toward more complex topics including climate change mitigation, green economy, ESG integration, and financial inclusion. Citation analysis further identifies influential works that shape the field, emphasizing major themes such as Industry 4.0, AI applications, and smart city development. Despite the potential benefits, challenges persist, including data privacy, energy consumption of digital infrastructures, ethical dilemmas, and socio-economic disparities in digital access. This study contributes to expanding interdisciplinary knowledge and provides strategic insights for policymakers, organizations, and academics to harness digital transformation as a catalyst for sustainable development.